Tropical Apocalypse : Haiti and the Caribbean End Times - Munro, Martin (Book collections on Project MUSE., 2015)
"This book offers both a history of apocalyptic culture in the Caribbean and an up-to-date account of the social, political, environmental, religious, and economic factors that have brought apocalypse back to prominence in the region"--